2020 25th International Conference on Pattern Recognition (ICPR) 2021
DOI: 10.1109/icpr48806.2021.9412381
|View full text |Cite
|
Sign up to set email alerts
|

How to define a rejection class based on model learning?

Abstract: In supervised classification, the learning process typically trains a classifier to optimize the accuracy of classifying data into the classes that appear in the learning set, and only them. While this framework fits many use cases, there are situations where the learning process is knowingly performed using a learning set that only represents the data that have been observed so far among a virtually unconstrained variety of possible samples. It is then crucial to define a classifier which has the ability to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In this context, a past contribution combined microscopy imaging with computer vision and machine learning techniques, and showed that compound treatments can induce distinctive phenotypical changes to a filamentous fungi, which in turn are crucial information that allow to raise a well-informed hypothesis on the possible biological targets of a compound [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a past contribution combined microscopy imaging with computer vision and machine learning techniques, and showed that compound treatments can induce distinctive phenotypical changes to a filamentous fungi, which in turn are crucial information that allow to raise a well-informed hypothesis on the possible biological targets of a compound [18].…”
Section: Introductionmentioning
confidence: 99%